2013
DOI: 10.7860/jcdr/2012/4391.2683
|View full text |Cite
|
Sign up to set email alerts
|

The Socio-Demographic Characteristics of the Clients of Female Sex Workers and their Perspectives, Behaviours and Attitude on HIV and AIDS: A Questionnaire Based Survey from Pokhara, Nepal

Abstract: HIV and AIDS is a cross cutting issue in the present situation rather than a health issue. One of the most at risk groups is the clients of female workers who frequently have risk behaviours like having sex with female sex workers. The sexual behaviour among these clients depends upon their attitude, knowledge and perception, which also influence several internal and external factors. In our study, the clients of the female sex workers had some extent of knowledge about the condom, sexually transmitted infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…As already confirmed by literature studies a high level of education has been observed among study group and the result also confirmed that high education trend to have a high perception and have a low risk of HIV/AIDs infection [32] [33] [34]. Previous studies also confirmed that CFSWs with high HIV knowledge perceived themselves at lower risk for HIV infection [35] [36].…”
Section: Discussionsupporting
confidence: 83%
“…As already confirmed by literature studies a high level of education has been observed among study group and the result also confirmed that high education trend to have a high perception and have a low risk of HIV/AIDs infection [32] [33] [34]. Previous studies also confirmed that CFSWs with high HIV knowledge perceived themselves at lower risk for HIV infection [35] [36].…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with prior reports, 15 , 25 Nepali men’s use of FSWs varied considerably across educational, economic, and marital status categories: men with higher educational and better economic status, and divorced men reported higher rates of sexual contact with FSWs. Although the overall prevalence of Nepali men’s use of FSWs was low, it was concentrated among these specific groups, signifying the potential effectiveness of specifically tailored interventions.…”
Section: Discussionsupporting
confidence: 82%
“…Research to date has revealed that the use of FSWs in Nepal may be common among truck drivers and migrant workers, and often involves young men. 15 – 17 These studies were focused primarily among higher risk groups (eg, transport workers, construction workers, and returnee migrant workers). 9 , 15 , 17 Hence, the degree to which this issue persists in the general population remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation